Hoax Digital Literacy on Instagram - Dedeh Fardiah; Ferry Darmawan; Rini Rinawati (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2021)
The development of communication technology brings forth new media with various multiplatforms. Information spreads instantaneously to all corners of the world through abundant media devices. In social media spaces, every individual can produce informational content and disseminate it, so it appears as a new phenomenon of citizen journalism. Individuals act as both producers and targets of social media content simultaneously. Ironically, due to freedom of expression on social media, various hoaxes appear intentionally or unintentionally and are widely distributed. This study aims to explore the official Instagram account that handles hoaxes in West Java Province and provide a digital literacy education in their post. This study uses the content analysis method, which efficiently investigates media content on both printed form and digital posts. In addition, it also uses descriptive content analysis to describe in detail a message or a specific content. The study object is Instagram @jabarsaberhoaks with an analysis unit of information items about hoaxes and various digital literacy on Instagram @jabarsaberhoaks in 2020.Â  In total, their number reaches 900 posts. The result of this study shows that the most common hoax is fake news, such as manipulated content, misleading content, fake news, and fabricated content with health, political, and economic themes. Explicitly or implicitly, digital literacy education about hoaxes can be obtained by accessing the information contained in Instagram accounts. The implication is that it is necessary to study the extent of this educational content responded by the public, so media messages can effectively and efficiently be in the form of educational media about interactive hoaxes.